Diverse bone microanatomy in cetaceans from the Eocene of Ukraine further documents early adaptations to fully aquatic lifestyle - Davydenko, Svitozar; Tretiakov, Roman; Gol’din, Pavel (Frontiers in Earth Science, 2023)
Basilosauridae, fully aquatic archaeocetes from the Eocene, had osteosclerotic or pachyosteosclerotic structure of ribs and, sometimes, other bones. Such a structure is far different from osteoporotic-like bones of modern cetaceans. A microanatomical and histological study was conducted on axial and limb skeleton of several basilosaurid specimens assigned to the genus Basilotritus, from Bartonian (late middle Eocene) deposits of Ukraine, remarkable for its pachyostotic bones. The postcranial skeleton of these specimens is a complex mosaic of diverse types of bone structure, which include pachyosteosclerotic, osteosclerotic and cancellous elements. The vertebrae have a pachyostotic layered cortex reaching its greatest thickness in the lumbar region. This cortex was strongly vascularized, and its layered structure is due to concentric circles mostly made by longitudinal vascular canals, in addition to cyclical growth lines. Heavy bones are concentrated in the dorsal and ventral areas. Swollen distal ends of thoracic ribs are interpreted as serving as ballast in the ventral area, as also previously proposed for Basilosaurus cetoides. Cortical bone tissue in vertebrae and ribs showed signs of intensive resorption and remodeling. This indicates the use of the axial skeleton not only for buoyancy control but also possibly for calcium and phosphorus recycling.